Comparison of Emergency Medical Services and Trauma Care Systems Among Pan-Asian Countries: An International, Multicenter, Population-Based Survey. (4th March 2017) - Sun, Kyong Min; Song, Kyoung Jun; Shin, Sang Do; Tanaka, Hideharu; Shaun, Goh E.; Chiang, Wen-Chu; Kajino, Kentaro; Jamaluddin, Sabariah Faizah; Kimura, Akio; Ro, Young Sun; Wi, Dae Han; Park, Ju Ok; et al.
ABSTRACT: Objective : Knowledge on the current trauma systems in Asian countries is limited. The objective of this study was to describe the emergency medical services (EMS) and trauma care systems among countries participating in the Pan-Asian Trauma Outcomes Study (PATOS) Clinical Research Network.Methods : The PATOS network consists of 33 participating sites from 14 countries. Standardized data was collected from each site using an EMS survey form and included general information (population, population density, urbanization, EMS service fee, etc.), dispatcher system, trauma care practice, trauma education program, existence of a trauma registry, and data on EMS transfers. Data is described with simple descriptive statistics.Results : All countries included urban sites. Nine countries included rural sites and only one country included wilderness site. Of the 33 sties, 18 sites had physician-based EMS systems. EMS services were free in 9 countries. Twelve sites had dispatch centers operated by government health departments. EMS dispatcher certification was required in 29 sites. Thirty-two sites had EMS documented protocols for trauma and 31 sites had field triage tools. Thirty sites had designated trauma centers. Twenty-one sites had helicopter EMS systems. Thirty-one sites require certification for trauma education programs. Only 23 sites maintained EMS-based trauma registries. In 20 sites, EMS medical directors reviewed and assured trauma registry quality. Of patients transported by EMS rate of injured patients ranged from 15% to 59%.Conclusion : Substantial variability exists in EMS systems in Asia, especially for injured patients. Futures studies are required to assess the impact of this variability on patient outcomes.